2015
DOI: 10.1007/s12032-015-0656-1
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 overexpression suppresses renal cancer cell proliferation and induces apoptosis

Abstract: FBXW7 gene (F-box and WD-40 domain protein 7) is also named HCDC4 and is a significant tumor suppressor gene, which can regulate human cell cycle, proliferation and differentiation. In this study, we tend to investigate protein expression and related biological functions of FBXW7 gene. FBXW7 expression level in renal cell carcinoma (RCC) tissues is highly related to its clinical pathologic grade (P = 0.0094) and TNM phase (P = 0.0080) and is highly lower than in paracancerous normal tissues through immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The prognostic significance of low FBXW7 expression has been reported in many types of solid tumors, such as breast, colorectal, cervical, and renal cancers. 12,13,38,39 We also observed that low FBXW7 expression was associated with shorter OS among patients with advanced OSCC, and for the first time, we demonstrated this relationship among patients with OSCC who underwent CRT. As the FBXW7 expression levels were significantly associated with the pathological response to preoperative CRT (Table 1), the difference in OS between the groups in the multivariate analysis may be partially due to the different responses to preoperative CRT in the groups with low and high FBXW7 expression.…”
Section: Discussionsupporting
confidence: 65%
“…The prognostic significance of low FBXW7 expression has been reported in many types of solid tumors, such as breast, colorectal, cervical, and renal cancers. 12,13,38,39 We also observed that low FBXW7 expression was associated with shorter OS among patients with advanced OSCC, and for the first time, we demonstrated this relationship among patients with OSCC who underwent CRT. As the FBXW7 expression levels were significantly associated with the pathological response to preoperative CRT (Table 1), the difference in OS between the groups in the multivariate analysis may be partially due to the different responses to preoperative CRT in the groups with low and high FBXW7 expression.…”
Section: Discussionsupporting
confidence: 65%
“…Of note, FBXW7 functions as a tumor suppressor in various types of human cancers, due to its capability to suppress cell growth, invasion and migration [31][32][33]. For example, FBXW7 overexpression can lead to the reduction in cell proliferation, migration and invasion in renal cancer [34], HCC [35], and gastric cancer [36]. In OC, FBXW7 was down-regulated in the OC tissues, and its low expression was negatively correlated with the malignant potential of OC [37].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, another primary reason for MDR is to reduce susceptibility to drug-induced apoptosis (21,22). Fu et al (35) confirmed that a reduced expression of JUN contributes to an extended G1 phase and induces apoptosis. In addition, activating MYC has been proved to generate apoptosis by triggering cytochrome c before activating caspase (36).…”
Section: Discussionmentioning
confidence: 71%